2011
DOI: 10.14214/sf.37
|View full text |Cite
|
Sign up to set email alerts
|

Host tree and insect genetic diversity on the borderline of natural distribution: a case study of Picea abies and Pityogenes chalcographus (Coleoptera, Scolytinae) in Greece

Abstract: Picea abies (L.) Karst. and Pityogenes chalcographus constitute a commonly observed host tree-insect association in Eurasia, with the natural distribution of the bark beetle overlapping that of Norway spruce. The southernmost borderline of their distributions occurs in the Elatia forest (Mt. Rodopi, Greece), where these interacting organisms may experience severe conditions due to the effects of climate change. In order to assess the dynamics of this host tree-insect association, the genetic diversity of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…For example, Keren et al [9] noticed that warm and dry summers are frequently followed by bark beetle outbreaks, which in turn cause a notable spruce decline. Indeed, studying the parallel genetic diversity of Norway spruce and Pityogenes chalcographus at the southernmost borderline of their distribution range, Avtzis and Aravanopoulos [10] found a significantly higher genetic diversity for the same gene in spruce bark beetle compared to the host, which might, in turn, provide a better evolutionary potential for adaptation of the insect to altered environmental conditions. Furthermore, Stojanović et al [11] reported that significant change of Norway spruce bioclimatic niche in Serbia might be expected by the end of 21st century.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Keren et al [9] noticed that warm and dry summers are frequently followed by bark beetle outbreaks, which in turn cause a notable spruce decline. Indeed, studying the parallel genetic diversity of Norway spruce and Pityogenes chalcographus at the southernmost borderline of their distribution range, Avtzis and Aravanopoulos [10] found a significantly higher genetic diversity for the same gene in spruce bark beetle compared to the host, which might, in turn, provide a better evolutionary potential for adaptation of the insect to altered environmental conditions. Furthermore, Stojanović et al [11] reported that significant change of Norway spruce bioclimatic niche in Serbia might be expected by the end of 21st century.…”
Section: Introductionmentioning
confidence: 99%
“…Universal primers were defined in conserved regions (exons) and were used to amplify mtDNA regions with conserved microsynteny. Polymorphism in amplified fragment has been revealed with various methods: PCR-RFLP (Boonruangrod et al, 2008;Godbout et al, 2005;San Jose-Maldia et al, 2009;Moriguchi et al, 2009;Naydenov et al, 2007), RFLP-SSR (Burban and Petit, 2003;Godbout et al, 2005;Jaramillo-Correa et al, 2003), mtDNA-SSR (Hosaka and Sanetomo, 2009), the variable number of tandem repeats (VNTR) in minisatelite regions (Bastien et al, 2003;Fievet et al, 2007;Honma et al, 2011;Yoshida et al, 2012), and finally in DNA sequences (Avtzis and Aravanopoulos, 2011;Eckert et al, 2008;Edwards et al, 2005;Goodall-Copestake et al, 2010;Gugger et al, 2011). The choice of the candidate loci was limited and was depending on the taxonomic level addressed by the phylogenetic study.…”
Section: Taxonomymentioning
confidence: 99%